Action Research in Information System Research - จอนจวบทรง ลั่นทม; ธรรมบุญวริศ ณธภร (Business Administration and Management Journal Review, 2018)
Action research (AR) is focused on action with collaboration between researchers and practitioners. However, AR has to be operated based on theories and theoretical framework. AR has been critiqued which lack of rigor in research methodology. For information system research with AR has been difficult to identify whether AR or consulting work. As a result, AR researchers should pay much attention on AR type and framework selection. This article will introduce AR types, such as action Science (AS) for information system research in order to increase the rigor of action research and clarify as the research instead of consulting work.